Turning vice into virtue: Institutional work and professional misconduct. (September 2019) - Harrington, Brooke
Why do professionals engage in or aid misconduct, rather than rejecting it as a threat to their legitimacy and labor market survival? This article contributes to the scholarly agenda by drawing on an ethnographic study of professionals who facilitate offshore tax avoidance for the ultra-wealthy. This form of expert advisory work has become highly controversial, and is increasingly classified as a form of professional wrongdoing. Building on theories of institutional work and categorization, the study theorizes practitioners' responses to field-level legitimacy threats. Specifically, the article models a process in which misconduct is recategorized in terms of the core norms that underpin professional legitimacy. Through this process, practitioners create institutional change by altering the way they see themselves and their work, transforming the 'vice' of tax avoidance into the professional 'virtues' of public service and expert neutrality. This model advances knowledge compared to previous research on professional misconduct, which was situated primarily at the organization level, and responds to calls for analysis of 'agentic self-categorization' processes in creating the micro-foundations for legitimacy in the professions.